Understanding India's Food Inflation : The Role of Demand and Supply Factors - Anand, Rahul (IMF Working Papers; Working Paper ;, 2016)
Over the past decade, India has seen a prolonged period of high inflation, to a large extent driven by persistently-high food inflation. This paper investigates the demand and supply factors behind the contribution of relative food inflation to headline CPI inflation. It concludes that in the absence of a stronger food supply growth response, food inflation may exceed non-food inflation by 2 1\2 -3 percentage points per year. The sustainability of a long-term inflation target of 4 percent under India's recently-adopted flexible inflation targeting framework will depend on enhancing food supply, agricultural market-based pricing, and reducing price distortions. A well-designed cereal buffer stock liquidation policy could also help mitigate food inflation volatility.